Unified vaccinators training in ITM against ECF in Tanzania - CGIAR Research Program on Livestock (2017)
Supporting the creation of a unified vaccinators' training course in the Infection and Treatment Method (ITM) against ECF in Tanzania. The Livestock Training Agency (LITA) is now providing this service.